Augmenting endogenous repair of soft tissues with nanofibre scaffolds. Issue 141 (25th April 2018) - Baldwin, Mathew; Snelling, Sarah; Dakin, Stephanie; Carr, Andrew
Abstract : As our ability to engineer nanoscale materials has developed we can now influence endogenous cellular processes with increasing precision. Consequently, the use of biomaterials to induce and guide the repair and regeneration of tissues is a rapidly developing area. This review focuses on soft tissue engineering, it will discuss the types of biomaterial scaffolds available before exploring physical, chemical and biological modifications to synthetic scaffolds. We will consider how these properties, in combination, can provide a precise design process, with the potential to meet the requirements of the injured and diseased soft tissue niche. Finally, we frame our discussions within clinical trial design and the regulatory framework, the consideration of which is fundamental to the successful translation of new biomaterials.